Socio-economic and Environmental Impact of Ecotourism in Nepal - Sapkota, Naniram (Nepalese Journal of Hospitality and Tourism Management, 2023)
Nepal is very rich in terms of its natural beauty and cultural diversity which have provided an enormous opportunity for tourism. Past literature works show that ecotourism helps enhance conservation of natural resources and biodiversity, preserve local cultures and alleviate poverty through an ethical and responsible approach of development. Acknowledging its potential benefits, Nepal has promoted ecotourism as a strategy to attract foreign capital particularly based on indigenous culture, heritage and environmental resources. However, ecotourism has demonstrated its shortcomings. Hence, this paper aimed to critically review the impact of eco-tourism on socio-economic and environmental aspects in Nepal. Based on the review of the various related literatures, this study concluded that ecotourism is crucial for natural resource management, biodiversity conservation, and increase in greenery in Nepal. It is a major contributor to the Nepalese economy, economic development and poverty alleviation. Its contribution to rural development, agricultural transformation, community enrichment and social empowerment is significant. However, it also consumes scarce resources, produces wastes, requires specific infrastructure, and increase pollution, and is likely to increase alcoholism, and create adverse impact on local traditional cultures and make local lifestyle vulnerable to Western influence.